Motion – All Patients with NASH Need to Have a Liver Biopsy: Arguments against the Motion - Jacqueline Laurin (Canadian Journal of Gastroenterology)
Most cases of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) are suspected on the basis of the exclusion of viral, autoimmune, metabolic and genetic causes of chronic liver disease in patients with chronic elevation of aminotransferase enzymes. However, the definitive diagnosis of NASH requires liver biopsy. Valuable blood tests include hepatitis B and C serology, iron profile, alpha 1-antitrypsin phenotype, ceruloplasmin, antinuclear antibody and antismooth muscle antibody, and serum protein electrophoresis. If these tests are negative or normal, and if there are no symptoms or signs of chronic liver disease, it is unlikely that a specifically treatable liver disease would be discovered at biopsy. The prevalence of NAFLD in the general population appears to be approximately 20%, and 2% to 3% of people have NASH. There is no proven specific therapy for the spectrum of nonalcoholic liver disease; therefore, the management of the patient with NASH is not likely to be changed after histological assessment. Bleeding, sometimes fatal, and other complications requiring hospitalization can occur, and liver biopsies should not be undertaken without clear clinical indications. The high cost of undertaking histological assessment of all persons with asymptomatic elevations of liver enzymes cannot be justified in view of the risks and limited clinical benefits.